Chemical composition and in vitro cytotoxic effects of the essential oil from Nectandra leucantha leaves. (January 2015) - Grecco, Simone dos S.; Martins, Euder Glendes A.; Girola, Natália; de Figueiredo, Carlos R.; Matsuo, Alisson L.; Soares, Marisi G.; Bertoldo, Bruno de C.; Sartorelli, Patricia; Lago, João Henrique G.
Abstract Context: Nectandra (Lauraceae) species have been used in folk medicine as an antidiarrheal, analgesic, antifungal, etc., and have many pharmacological proprieties. Objective: Investigation of the chemical composition and cytotoxicity of essential oil from Nectandra leucantha Nees & Mart. leaves. This is the first study involving N. leucantha reported in the literature. Material and methods: The essential oil of N. leucantha leaves was obtained by hydrodistillation. Its chemical composition was determined using a combination of GC/FID, GC/MS, and determination of Kovats index (KI). In vitro cytotoxic activity was evaluated against six cancer cell lines – murine melanoma (B16F10-Nex2), human glioblastome (U-87), human cervical carcinoma (HeLa), human colon carcinoma (HCT), human breast adenocarcinoma (MCF7), and human cervical tumor (Siha) as well as against one non-tumorigenic cell line – human foreskin fibroblast (HFF). Results: Thirty-three compounds were identified primarily sesquiterpenes (81.41%), the main compounds being bicyclogermacrene (28.44%), germacrene A (7.34%), spathulenol (5.82%), and globulol (5.25%). Furthermore, monoterpenes were also found in the analyzed oil (12.84%), predominantly α- and β-pinenes (6.59 and 4.57%, respectively). The crude essential oil displayed significant cytotoxic activity against B16F10-Nex2 (IC50 33 ± 1 μg/mL) and U87 (IC50 75.95 ± 0.03 μg/mL) and HeLa (IC50 60 ± 12 μg/mL) cell lines. The main identified compound, bicyclogermacrene, displayed IC50 ranging from 3.1 ± 0.2 to 21 ± 6 μg/mL. Discussion and conclusion: The results indicate that the crude oils from leaves of N. leucantha displayed cytotoxic activity being bicyclogermacrene, the main compound identified in the crude oil responsible, at least in part, for this potential.